2008
DOI: 10.1038/oby.2008.23
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Lean Body Mass to Insulin Resistance in Postmenopausal Women With Visceral Obesity: A Monet Study

Abstract: Some insulin-resistant obese postmenopausal (PM) women are characterized by an android body fat distribution type and higher levels of lean body mass (LBM) compared to insulin-sensitive obese PM women. This study investigates the independent contribution of LBM to the detrimental effect of visceral fat (VF) levels on the metabolic profile. One hundred and three PM women (age: 58.0 ± 4.9 years) were studied and categorized in four groups on the basis of their VF (higher vs. lower) and lean BMI (LBMI = LBM (kg)/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
72
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 59 publications
(90 reference statements)
15
72
1
3
Order By: Relevance
“…7,9,20 For example, our group has previously shown that the combination of high LBM and high visceral adipose tissue was associated with further deterioration in the metabolic profile compared with the combination of high visceral adipose tissue and normal LBM. 34 Whether increased LBM is a consequence of metabolic disturbances or whether it has a causal function in the development of the MAO phenotype remains to be investigated. Interestingly, a recent study showed that muscle strength was significantly higher in MHO individuals despite lower levels of LBM.…”
Section: Evidence Of a Subgroup Of Metabolically Healthy But Obese Inmentioning
confidence: 99%
“…7,9,20 For example, our group has previously shown that the combination of high LBM and high visceral adipose tissue was associated with further deterioration in the metabolic profile compared with the combination of high visceral adipose tissue and normal LBM. 34 Whether increased LBM is a consequence of metabolic disturbances or whether it has a causal function in the development of the MAO phenotype remains to be investigated. Interestingly, a recent study showed that muscle strength was significantly higher in MHO individuals despite lower levels of LBM.…”
Section: Evidence Of a Subgroup Of Metabolically Healthy But Obese Inmentioning
confidence: 99%
“…The findings of these studies were validated in more recent studies in obese post-menopausal women using dualenergy X-ray absorptiometry to measure body composition and computed tomography (CT) to measure body fat distribution [36,37]. Lean mass was independently associated with insulin levels and glucose homeostasis, and the association of visceral fat with IR was enhanced by an increase in lean mass in post-menopausal women [37]. All these studies were done in obese post-menopausal women.…”
Section: Discussionmentioning
confidence: 83%
“…In the case of postmenopausal women, fat redistribution and more particularly increased visceral fat is related to increased insulin resistance and high NEFA circulating levels (30,31). This could affect the performance of fasting indices as previously reported (3,6).…”
Section: Discussionmentioning
confidence: 99%